Predictors of specialist referral for developmental and behavioural problems in a Queensland urban Aboriginal and Torres Strait Islander community: A cross-sectional study - Liddle, K.; Askew, D.; Betts, K.; Hayman, N.; Alati, Rosa (The Royal Australian College of General Practitioners, 2014)
Background: The prevalence of developmental and/or behavioural problems is greater among Aboriginal and Torres Strait Islander children, compared with their non-Indigenous counterparts. We aimed to identify predictors of specialist paediatric referral for these problems that could enable primary health professionals to identify at-risk children and implement early interventions. Methods: A cross-sectional study of urban Aboriginal and Torres Strait Islander children aged 0-14 years having annual child health checks from September 2010 to February 2012 was undertaken. Predictors of paediatric referral were identified using univariable and multivariable analyses. Results: Of the 183 eligible children, 30% were referred to a paediatrician. Parental/carer mental illness was self-reported in 36% of cases and these children were more likely to be referred (OR = 3.07; 95% CI: 1.44, 6.57). Discussion: The strong association between paediatric referral for behavioural and/or developmental problems and self-reported parental/carer mental illness highlights the intergenerational nature of health and social disadvantage.